Analisis Perbedaan Kinerja Keuangan Perusahaan Antara Sebelum Dan Sesudah Berpartisipasi Dalam Indonesian Suistanabillity Reporting Awards (ISRA) - Oktriani, Megi; Maryati, Ulfi (Jurusan Akuntansi Politeknik Negeri Padang, 2016)
This study aims to test whether there are differences in corporate financial performance between before and after participating in ISRA. This study uses secondary data. The variables in this research are financial performance from profitability ratio that includes return on asset (ROA), return on equity (ROE), net profit margin (NPM). The sample of this research consist of 13 companies with purposive sampling method that is company which become participant of Indonesian Sustainability Reporting Awards consistently three consecutive year in 2007-2011 period. Data collection of research samples can be accessed through the company website and website National Center of Sustainability Reporting and the company publishes Annual Financial Reports in 2004-2014 that can be accessed through the company website. Hypothesis testing was done by paired sample t-test technique using IBM SPSS version 20 software. The result showed that there was no difference of company performance between before and after participated in Indonesian Sustainability Reporting Awards.